Alternative Approach to Sustainable Urban Mobility in Developing Countries - Fadhil, Dimas Nu’man; Jinca, Arimbi; Prakoso, Puguh; Hoegeng, Julianto (PT Penjaminan Infrastruktur Indonesia (Persero), 2021)
Cities in developing countries are facing intertwined urban mobility challenges: urban sprawl and traffic jam. Having not enough reliable and standardized public transport supply means the residents are forced to opt for traveling by private vehicles such as cars or motorcycles. There is a swell of tailpipe emission and economic losses due to traffic jam. Overcoming urban sprawl and at the same time building massive public transport is not an easy feat to accomplish, as both require immense investments and years of construction. Therefore, cities must have innovative plans to increase public-transport coverage and articulate density through paratransit formalization & digitalization, demand management, and land consolidation.